The Comprehensiveness Dilemma of Cost-Benefit Analysis - Sager, Tore (European Journal of Transport and Infrastructure Research, 2013)
Most project impacts on environment, climate, and health are not valued in markets or in choice situations similar to market transactions. Analysts have to go beyond revealed preferences to stated preference interviews and even to deliberative processes in order to elicit preferences from which the trade-off values (‘prices’) of the expanded cost-benefit analysis (CBA) can be deduced. The comprehensiveness dilemma of social CBA arises with the choice between calculation of ‘prices’ from revealed preferences and communicative construction of ‘prices’ on the basis of preferences stated in deliberation. New methods for eliciting preferences, such as deliberative monetary valuation, yield preferences influenced by ethical and political values. The interpretation of the analytic results then becomes problematic. The comprehensiveness dilemma is that planners must choose between a narrow CBA making good economic sense, and a comprehensive CBA with dubious economic content. By aiming for completeness, CBA changes character from being a summation of changes in individual wellbeing to being a mix of this and the summation of monetary expressions of ethical and political viewpoints and attitudes.